Goodbye, good men how liberals brought corruption into the Catholic Church - Rose, Michael S. (Regnery Pub., 2002)
As the controversy surrounding the Catholic Church deepens, this new book charges that liberal bishops, priests, and feminist nuns "discriminated against" and "black-balled" generations of devout Catholic men in favor of seminarians that reject Church teachings. Michael Rose, an investigative journalist, conducted more than 150 personal interviews that included 125 seminarians representing some fifty dioceses and twenty-two major seminaries over two years. Rose found that the shortage of priests is an internal crisis created by a network of pro-feminist, pro-homosexual liberals who favor artificial birth control and ordination of women.
Includes bibliographical references and index
Keywords: Katholische Kirche; Liberalism (Religion) -- Catholic Church; Vocation, Ecclesiastical; Homosexualität; Priester; USA